Relationship between longer sleep and serum neurofilament light chain in american adults: evidence from the 2013-2014 US national health and nutrition examination survey - Chunyan Zhang; Yitian Yang; Huanxian Liu; Jiaqiang Zhang (BMC, 2024)
Abstract Background Sleep disturbance is linked to neurodegenerative diseases and the related brain pathophysiology. Serum neurofilament light chain (NfL) is a reliable biomarker for neurological disorders. This study examined the association between sleep characteristics and serum NfL levels in American adults. Methods In this cross-sectional study, data from the 2013-2014 US National Health and Nutrition Examination Survey were utilized. Participants were categorized into short (≤ 6 h), normal (7-8 h), and long (≥ 9 h) sleep groups based on their self-reported sleep durations. Sleep duration, trouble sleeping, and diagnosed sleep disorders were queried, forming "sleep pattern (healthy, moderate, and poor)." The association between sleep characteristics and serum NfL levels was assessed using multivariate linear regression models. Stratification and sensitivity analyses were conducted to determine the stability of results. Results Overall, 1637 participants were included; among them, 48.2% were male and 51.8% were female (mean ± SD, age: 46.9 ± 15.5 years) and 38.8% reported sleeping for ≤ 6 h, 54.4% for 7-8 h, and 6.8% for ≥ 9 h. Participants with longer sleep duration, poor sleep pattern, diagnosed sleep disorders, or trouble sleeping exhibited higher serum NfL levels. A positive correlation was found between extended sleep and elevated serum NfL levels (Adjusted β = 4.82, 95%CI: 2.2, 7.44, P < 0.001), with no significant correlation observed in the short-sleep group or those with poor sleep pattern. Stratified and sensitivity analyses confirmed the robustness of the relationship between longer sleep and elevated serum NfL levels. Conclusions A long sleep duration is associated with higher serum NfL levels than a normal sleep duration in American adults.